Desain dan Pengembangan Sistem Aktuator "Soft-Robotic" Berbiaya Rendah untuk Rehabilitasi Tangan: Prototipe "E-Glove" - Aldo Dwi Putra Pasaribu; Wahyu Dwi Lestari (JURNAL ILMIAH MOMENTUM, 2025)
Stroke and traumatic brain injury often lead to hand motor impairments that limit independence and quality of life.This study presents a portable, low-cost actuator system for the E‑Glove: a soft robotic glove designed to deliver continuous passive motion (CPM) for hand rehabilitation. The actuator design was envisioned to be capable of producing sufficient torque to overcome severe stiffness (resistive force ≥8 N), user-friendly control, and portability. The actuator module consists of two TowerPro MG996R servo motors controlled by an Arduino Nano, with capacitive touch sensors allowing three discrete speed settings (35.7, 45.5, and 50.0 degrees/s) and RGB LED feedback. Biomechanical analysis determined a lever arm of 0.07 m and calculated a maximum resistive torque of 12.28 N-m, resulting in a safety factor >1 for severe flexure. Prototype testing confirmed reliable operation at all speed levels and safe disengagement upon power‑off. The detachable actuator housing, powered via USB‑C, supports home‑based therapy and remote monitoring. This work addresses critical barriers to accessibility, promoting high‑frequency rehabilitation outside clinical settings.